Comparative Study of Fish Eel Amino Acid Profile (Anguilla marmorata (Q.) Gaimard) on Silver eel Phase from Palu River and Poso Lake - Jamaluddin; Cindra Rusli; Yonelian Yuyun; Agustinus Widodo (Journal of Pharmacy and Nutrition Sciences, 2019)
Amino acid is an organic component containing amine and carboxyl groups. Amino acids are needed by the human body. One animal that has the amino acid content is eel (Anguilla marmorata (Q.) Gaimard) from Palu River and Poso Lake in Central Sulawesi which are endemic fish. This study aims to determine the comparison of amino acid profile in eel (Anguilla marmorata (Q.) Gaimard) on silver eel phase. Testing amino acid profile using High Performance Liquid Chromatography (HPLC). The results showed that the eel (Anguilla marmorata (Q.) Gaimard) on phase of silver eel from the Palu River and Poso Lake contained 18 kinds of amino acid consisting of 9 kinds of essential amino acids and 9 types of non-essential amino acids. Data comparison shows a significant difference in glycine P = 0.000 and has no significant differences in the valine at P = 0.132.